2015
DOI: 10.1016/j.molonc.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the tumor microenvironment and inhibition of EGF/EGFR pathway: Novel anti‐tumor mechanisms of Cannabidiol in breast cancer

Abstract: The anti-tumor role and mechanisms of Cannabidiol (CBD), a non-psychotropic cannabinoid compound, are not well studied especially in triple-negative breast cancer (TNBC). In the present study, we analyzed CBD’s anti-tumorigenic activity against highly aggressive breast cancer cell lines including TNBC subtype. We show here -for the first time- that CBD significantly inhibits epidermal growth factor (EGF)-induced proliferation and chemotaxis of breast cancer cells. Further studies revealed that CBD inhibits EGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
192
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 197 publications
(198 citation statements)
references
References 58 publications
5
192
0
1
Order By: Relevance
“…Other recent studies indicated that CBD significantly inhibits epidermal growth factor (EGF)-induced proliferation and chemotaxis of breast cancer cells. In addition, it was shown that CBD inhibits EGF-induced activation of EGFR, ERK, AKT and NF-kB signaling pathways as well as MMP2 and MMP9 secretion (Elbaz et al, 2015). CBD also inhibited tumour growth and metastasis in different mouse model systems.…”
Section: Cannabinoids and Breast Cancermentioning
confidence: 98%
See 1 more Smart Citation
“…Other recent studies indicated that CBD significantly inhibits epidermal growth factor (EGF)-induced proliferation and chemotaxis of breast cancer cells. In addition, it was shown that CBD inhibits EGF-induced activation of EGFR, ERK, AKT and NF-kB signaling pathways as well as MMP2 and MMP9 secretion (Elbaz et al, 2015). CBD also inhibited tumour growth and metastasis in different mouse model systems.…”
Section: Cannabinoids and Breast Cancermentioning
confidence: 98%
“…CBD also inhibited tumour growth and metastasis in different mouse model systems. Analysis of molecular mechanisms revealed that CBD significantly inhibits the recruitment of tumour-associated macrophages in primary tumour stroma and secondary lung metastases (Elbaz et al, 2015). Figure 3 summarizes the important pathways in cannabinoid induced cytotoxicity.…”
Section: Cannabinoids and Breast Cancermentioning
confidence: 99%
“…Furthermore, CBD is able to inhibit cancer cell invasion and metastasis (478,548,715). These actions, in highly aggressive human breast cancer cells, are in part mediated by inhibition of epidermal growth factor (EGF), NF-B, ERK/AKT, and matrix metalloproteinase 2 and 9 signaling pathways (238). CBD also reduces angiogenesis through actions on both tumor and endothelial cells (809) (FIGURE 1).…”
Section: Cancermentioning
confidence: 99%
“…Our studies showed that LDHA downregulation inhibits cell migration, invasion and tube formation. Furthermore, our data showed that depletion of LDHA decreased the expression of MMP-2 and MMP-9, suggesting that LDHA may be involved in RCC invasion through inducing enzyme-based degradation of the extracellular matrix [23,24] . Furthermore, it is worth noting that LDHA depletion with siRNA leads to diminished VEGF and VE-cadherin levels, which are known to modulate vascular angiogenesis [25] and tumor development [26,27] .…”
Section: Discussionmentioning
confidence: 64%